An Error Analysis Of The Cohesive Devices Made By The Students In Writing Paragraph (A Study Of English Department Students Of Letters Faculty) - Rusdiah Rusdiah; Malombassang Malombassang (Tamaddun Life, 2018)
This research investigates cohesive devices errors in paragraphs written by the seventh semester students at UMI Makassar. This graduating paper intends to be a descriptive qualitative research which consist of a detail linguistic description and explanation of cohesive devices errors. It explains how cohesion is used erroneously in the students’ writing. The objectives of this research are to know whether there are any cohesive errors in English essays written by the seventh semester students at UMI Makassar, to find out the types of cohesive devices error committed in those paragraphs, and to describe the dominant of errors in using cohesive devices in those paragraphs. The results show that a total of 25 errors are identified in those paragraphs include errors on the use of reference, conjunction and lexical cohesion. Errors on the use of substitution and ellipsis are not found. The percentage of errors on the use of reference is 64%, conjunction 24%, and lexical cohesion 12%. From percentage of each types of errors on the use of cohesive devices, reference becomes the first dominant error, conjunction as the second dominant error, and lexical cohesion as the last dominant error.